Policy Implementation: The Strengthen Communication In Fishermen Insurance Government Program (BPAN) Tanggetada District, Kolaka Regency - Anis Ribcalia Septiana; Maria Margareta Reginaldis; Rustam Tohopi (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
The implementation of communication strengthening policies in the Fishermen Insurance of Government Assistance program in Tanggetada District, Kolaka Regency. The methods used in this study were analyzed using qualitative descriptive techniques. The informants in this study consisted of the Fisheries Secretary, Head of Small Fishermen Empowerment, Partnership Section, Science and Technology and Small Business Information in the Fisheries Sector, Small Fishermen Training and Assistance Section, Tanggetada District Extension Officer, Fishermen. Types and sources of data used in the study use primary and secondary data. The results of communication research in the socialization of the implementation of the Fishermen Insurance Government Assistance program (BPAN) have not been going well because information about BPAN has not been distributed to all fishermen in Tanggetada District. Communication is critical to the success of achieving the goals of implementation. For effective implementation, those who must be responsible for the implementation of a policy must know what to do. The government to implement policies must be conveyed clearly, accurately, and consistently to capable people. So the implementation of the Fishermen Insurance Government Assistance program (BPAN) carries out socialization actions to fishermen and prepares coordination for fishermen insurance recipients.